THE TRANSFORMATION OF THE MARKETING STRATEGY OF THE TELECOMMUNICATIONS COMPANY - O. K. Lugovskaya; M. A. Simakina (Вестник университета)
The experience of building the marketing strategy by the Russian telecommunications company Tele2 has been considered. Based on the description of the varied stages of the company’s development, the strategic choices of various years has been substantiated. The central point has been focused on determining the position of Tele2 in the telecommunications services market. It has been compared the approach to building the marketing strategy in Tele2 and other market participants. The new step of the company in the creation of the marketing strategy related to solving the problem of saturation of the telecommunications market due to the use of the concept of «Lifestyle enabler» has been analyzed.